A HUMAN‐FOCUSED, HOLISTIC MODEL OF COMMUNITY RESILIENCE. Issue 4 (December 2016) - McDermott, Tom; Folds, Dennis; Hutto, C.J.; Nadolski, Molly
ABSTRACT: This paper presents a model‐based systems engineering framework used to integrate physical, socio‐ecological, and psychological factors of community resilience in urban areas. The first year of a multi‐year project, the use of systems engineering methods to produce a combined human development and infrastructure development model for city resilience building provides an interesting case study for evolving systems engineering methods. The project used a sociotechnical‐modeling framework to capture social factors of community sustainability and resilience in the context of critical infrastructure renewal. Two system constructs of human capital, standard of living, and subjective well‐being, were linked to environmental, infrastructure, economic, and institutional factors to represent human capital aspects of community resilience at multiple scales. The framework identified causal relationships between individual micro‐scale indicators of infrastructure and social program development, and aggregate effects of human capital development. The goal is to define a full set of evaluation factors and computer‐based decision analysis tools for macro‐scale decision criteria for social, behavioral, and economic decision‐making in community infrastructures.